Cycling into the future: Integrating bicycles into the road network of Tangará da Serra–MT, a strategy for reducing CO₂ emissions - Nascimento, Alex Sandro Morais do; Carignani , Gisele; Souza, Natallia Sanches e; Dias, Wesley Afonso da Silva (Scientific Journal ANAP, 2025)
Objective – Present a feasibility study and propose the application of cycle path treatment for some roads in the municipality of Tangará da Serra - MT Methodology – Bibliographical references, field survey and qualitative research were used. Originality/Relevance – There are many studies on urban mobility in large cities, but few focused on new and medium-sized cities. In this sense, the theme contributes to the debate on sustainable urban mobility. Results – The low concentration of cycling infrastructure can be seen, but there is the possibility of a redistribution of spaces that would allow the insertion of bicycle infrastructure into the urban network. Theoretical/Methodological Contributions – Demonstration through images and surveys that the city can provide cycling infrastructure with minimal interventions. Social and Environmental Contributions – The findings highlight the importance of ensuring accessibility and urban mobility, proposing a mode of travel without impacting the environment